Results of application of external fixation in treating closed lower-leg fractures - Mladenko Lazić; Saša Vidić; Nikola Gavrić; Aleksandra Hadžiavdvić (Биомедицинска истраживања, 2013)
Introduction: . Lower-leg fractures represent the most often fractures of long bones. The most frequent fractures are those in middle-aged patients when their work and life activities are very intensive. The aim of the study was to determine the result of the treatment of closed lower-leg fractures with external fixation. Methods: . These patients in whom we did not get a satisfactory orthopedic reposition, and whose trea tment could not be continued non-surgically, were prepared for surgical treatment. After a pre-surgical preparation, blood reposition was done and external fixation was made in a typical way. External fixation was taken off 4 to 8 weeks later and then a Patellar Tendon Bearing (PTB) cast was placed until fracture was healed. Healing was verified by a clinical and radiological examination. Results: . This method was applied in 68 patients with closed lower-leg fracture, out of a total of 124 fractures. After a four-month medical treatment, we had 4 pseudoarthrosis of the Tibia whereas 64 fra ctures healed regularly. Pseudoarthrosis was treated surgically with fibula osteotomy and then with the application of PTB cast for walking after they healed. Conclusion: . Once the cast immobilization was removed, a rehabilitation treatment was implemented after which the patients had a satisfying function of a knee and an ankle joint without leg shortening.
Keywords: closed lower – leg fractures; external fixation